The Impact of Experience and Trust on Loyalty through Satisfaction as an Intervening Variable in Generation Z - Saputra; Irwan Christanto Edy (International Journal of Business Studies, 2026)
The purpose of this study is to determine the effect of experience and trust on Generation Z user loyalty through satisfaction as a mediating variable, in a study comparing two digital platforms: Shopee and TikTok Shop. This study used a quantitative approach with a Likert-scale questionnaire distributed to active users of both platforms in Karanganyar Indonesia Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that experience has a positive and significant effect on satisfaction. Experience also has a positive and significant effect on loyalty. Trust has a positive and significant effect on user satisfaction. Trust also has a positive and significant effect on loyalty. Conversely, user satisfaction has no significant effect on loyalty. Experience has no significant effect on loyalty mediated by satisfaction. Similarly, trust has no significant effect on loyalty mediated by satisfaction. These findings indicate that experience and trust directly have a positive and significant effect on user loyalty. Meanwhile, the influence through satisfaction as a mediating variable was insignificant, confirming that the primary factors in building loyalty are direct experience and trust.